Domino Servite School: an evaluative case study of a private Christian secondary school in rural Natal - Davidson, Michael R (Rhodes University, Faculty of Education, Department of Education, 1996)
Domino Servite School (DSS) is a private school, founded in 1986, and situated on KwaSizabantu (KSB) mission station in the Natal midlands. This research into DSS is a case study which aims to present an illuminative evaluation in the Whole School genre, within that branch of educational research concerned with effective schools. The project aimed to make use of a compatibility paradigm accommodating nomothetic and anthropological data. In attempting triangulation of methodological approaches, it tried to establish the extent to which DSS may be considered an efficient and effective 'New Private' school. It also aimed to understand the school's raison d'eÌŒtre. In order to illuminate the relevance and social processes of DSS, evaluation made use of internal and external referents. The internal investigation sought to make judgements in reference to the efficiency of the school as an organisation. On the macro-level, whole school evaluation required extensive curriculum evaluation. On the micro-level, appraisal of teaching and assessment of pupil performance was undertaken. This internal investigation required a critical analysis of the school's formal, informal and hidden curriculum. The external evaluation sought to make judgement in reference to the effectiveness of DSS. On the macro-level, this required evaluation of the findings of the internal investigation in terms of a broader South African context. Implications, for example of the school's 'private' status, and its 'Christian' curriculum in respect of multi-culturalism, education for nationhood , and ethnicity were examined. The analysis of these dimensions paid attention to the school's spatial context in terms of both its 'rural' and missionary setting. Here the focus was on the school's formal curriculum. Analysis of the inter-relational context paid attention to its informal curriculum or the way in which the school deals with the commonality and diversity of its clientele and staff. The inter-relational context of the school examined the hidden curriculum, or the relationship between the school and the broader South African Community. A critical ethnographic account of this institution was therefore possible because of the dual focus on the internal and external evaluation reference points. Internal evaluation made extensive use of direct (non-participant) observation, structured and nonstructured interviews, questionnaires, and documentary analysis. Indirect (participant) observation, in particular Clinical Supervision (CS), was also used. Indirect (non-participant) observation made extensive use of Flanders' Interaction Analysis Categories (FIAC). Teacher self-evaluation was also included, while analysis of pupil performance made use of 'standardised' achievement testing and a tracer study. External evaluation required detailed study of local and international literature on issues relating to private schooling, rural and multi-cultural education, education for nationhood and ethnicity. The research found that much of the school's curriculum path is incongruous with its rural context largely because of its association with the former Department of Education and Training (DET), and because of its missionary heritage. As such the school is presently (1) located within a questionable (formal) curriculum tradition which has little relevance to, nor potential for, the transformational needs of either rural Natal or South Africa in general. However, this does not preclude the possibility of the school making a contribution to education for development in South Africa. (2) The school advocates a mono-cultural Christian value system and modified cultural pluralism which attempts to assimilate pupils from diverse socio-economic and ideologically homogeneous backgrounds. Multi-cultural education, plural values, religious and values democracy are therefore not part of the school's raison d'eÌŒtre. (3) The school, through its associated organisation Christians for Truth (CFT), represents a social view espousing either a modified cultural pluralism or multi-nationalism which allows for allegiance to a transcendent value system without compromising group. values and associations. This means that the school aims at assimilating or amalgamating diversity into a mono-cultural unity that transcends group identity. This transcendent culture is defined in Christian terms. The study recommends inter alia, further investigation into the educational implications of_values neutrality and the particularism of secular humanism; a comparative analysis of a random sample of private missionary schools and ordinary state controlled rural schools so that more generalisable results might be obtained; and a more thorough investigation into the parental and pupil contributions to the school, their attitudes and perspectives on missionary education and their feelings about the management styles evident in the organisation.
Keywords: Christian education -- South Africa; Church schools -- South Africa; Education -- South Africa -- Kwazulu Natal; Private schools -- South Africa